2016
DOI: 10.3748/wjg.v22.i18.4610
|View full text |Cite
|
Sign up to set email alerts
|

Isolated splenic metastasis from colon cancer: Case report

Abstract: Isolated splenic metastases from colorectal cancer are very rare clinical entities and when they are present, they usually manifest widely disseminated disease. In this paper we report a case of metachronous solitary isolated splenic metastasis from colon cancer in a 64-year-old woman who was successfully treated by laparoscopic splenectomy. We discuss the pathological and clinical aspects of this condition. We furthermore comment on the diagnostic and therapeutic options of this rare entity through our observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 28 publications
4
21
0
7
Order By: Relevance
“…According to Indudhara et al, it is the retrograde fl ow of blood through the inferior mesenteric vein and splenic vein that carries neoplastic cells to spleen [12]. Many authors are of the opinion that metachronous splenic metastasis is more CEA level (4.6-223 ng/mL) in colonic adenocarcinoma [13], as was also observed in our patient (184 ng/mL). CEA has been supposed to modulates the immune response and suppresses the humoral response as well as lymphocyte and NK cell activity [14].…”
Section: Discussionsupporting
confidence: 74%
“…According to Indudhara et al, it is the retrograde fl ow of blood through the inferior mesenteric vein and splenic vein that carries neoplastic cells to spleen [12]. Many authors are of the opinion that metachronous splenic metastasis is more CEA level (4.6-223 ng/mL) in colonic adenocarcinoma [13], as was also observed in our patient (184 ng/mL). CEA has been supposed to modulates the immune response and suppresses the humoral response as well as lymphocyte and NK cell activity [14].…”
Section: Discussionsupporting
confidence: 74%
“…However, Abi saad et al [ 7 ] reported that splenectomy for isolated splenic metastasis can achieve long-term survival. Furthermore, Jiddou et al [ 8 ] reported 31 cases of isolated splenic metastasis from colorectal cancer, and splenectomy was performed in all cases. In addition, there are reports of laparoscopic approach too [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Jiddou et al [ 8 ] reported 31 cases of isolated splenic metastasis from colorectal cancer, and splenectomy was performed in all cases. In addition, there are reports of laparoscopic approach too [ 8 , 9 ]. Therefore, we performed laparoscopic splenectomy for the cure of isolated splenic metastasis, and yet histopathological examination of the spleen showed a sarcoid reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The most common metastatic organ of CRC is the liver, and it has been reported that almost 50% of patients diagnosed with CRC experienced simultaneous or heterogeneous liver metastases[ 3 , 7 ]. Splenic metastases in patients with malignant tumors generally indicate multiple metastases[ 1 , 2 ]. A splenic primary tumor or metastasis a rare disease, and the most common sources of splenic metastasis are melanoma (34%), breast cancer (12%), ovarian cancer (12%), CRC (10%), and lung cancer (9%)[ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Splenic metastases in patients with malignant tumors generally indicate multiple metastases[ 1 , 2 ]. Isolated splenic metastasis after radical colon adenocarcinoma resection is a rare clinical entity[ 3 ].…”
Section: Introductionmentioning
confidence: 99%